2021
DOI: 10.1097/pq9.0000000000000456
|View full text |Cite
|
Sign up to set email alerts
|

Improving Discharge Instructions Following a Concussion Diagnosis in the Pediatric Emergency Department: A Pre-post Intervention Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…No other published randomized trial has tested the impact of implementing a clinical pathway for pediatric concussion in the ED, although a prior quality improvement study showed a simple intervention increased the completeness of discharge instructions [ 29 ]. In our study, the design and implementation of the clinical pathway were guided by an evidence-based, theory-driven approach, but also relied on extensive input from site physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…No other published randomized trial has tested the impact of implementing a clinical pathway for pediatric concussion in the ED, although a prior quality improvement study showed a simple intervention increased the completeness of discharge instructions [ 29 ]. In our study, the design and implementation of the clinical pathway were guided by an evidence-based, theory-driven approach, but also relied on extensive input from site physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%